Students' Perceptions And Motivation towards Teaching Arabic Vocabulary Through Gamification - Ghofur, Abdul; Kholis, Muhammad Nur; Sodik, Achmad Ja'far; Shiddiq, Jamaluddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The utilization of digital-based game systems to enhance Arabic language learning outcomes has become a prevalent trend in recent times. This research aims to explore students' perceptions and motivations regarding the implementation of gamification systems in Arabic vocabulary learning. Specifically, the study investigates how students perceive and what motivates them after using Kahoot! App and Wordwall in their Arabic vocabulary learning journey. The research involved 30 students enrolled in the program of Arabic Language and Literature at UIN Raden Mas Said Surakarta, Indonesia. Data was collected by distributing questionnaires to students after using both applications during Arabic vocabulary lessons. Afterward, the data was subjected to analysis utilizing descriptive statistics. The findings revealed that, on average, students held a highly positive perception and exhibited significant motivation towards Kahoot! And Wordwall. However, in general, students preferred Kahoot! over Wordwall. This discovery is a valuable recommendation for teachers, lecturers, and practitioners involved in Arabic language learning, suggesting that these gamification systems be included as an integral part of the curriculum to support the Arabic learning process.